Testing of a lightweight SiC power module for avionic applications - Gurpinar, Emre; Lopez Arevalo, Saul; Li, Jianfeng; De, D.; Castellazzi, Alberto; Mills, Liam (2014)
Functional and performance tests of a three-phase, two-level power module based on CREE 1.2kV SiC MOSFETs for avionic applications is presented in this paper. SiC devices have superior properties over conventional Si devices at high voltage operations and these properties make SiC devices at-tractive for avionic industry in order to reduce size of power electronic converters while maintaining high efficiency. This paper starts with a brief explanation of thermo-mechanical de¬sign approach of SiC power module. Thermo-mechanical de¬sign is followed by test setup and experimental results for dif¬ferent load and switching frequency conditions. The module is tested up to 540V DC link voltage, 6kW output power with 100kHz switching frequency. Experimental results show that the module can be successfully operated with high efficiency at high switching frequencies.